Exploring Cultural Relevance of Outdoor Games in Early Childhood Education: A Study of Yoruba Traditional Games in Oyo Town, Nigeria - Saheed Olawale Olatunji; Gbemisola Olufunmilayo Leye-Akinlabi; Elizabeth Olaoluwa Adubuola; Opeyemi Omobolanle Oyewusi (Journal of Early Childhood Development and Education, 2026)
Background: Yoruba traditional outdoor games are important cultural practices that contribute to children’s socialization, moral upbringing, and indigenous learning. However, the increasing influence of digital entertainment and modern educational practices has reduced their use in early childhood education. Objective: This study examined the cultural relevance of Yoruba traditional outdoor games in early childhood education in Oyo Town, Nigeria. Specifically, the study explored their cultural significance, perceived educational benefits, and the challenges hindering their integration into early childhood education curricula. Methods: A descriptive survey research design was adopted. The population consisted of early childhood education stakeholders, including preschool teachers, caregivers, and school administrators. A sample was selected through simple random sampling. Data were collected using a structured questionnaire titled Cultural Relevance of Yoruba Traditional Outdoor Games Questionnaire (CRYTOGQ). The instrument was validated by experts and tested for reliability using Cronbach Alpha, yielding a coefficient of 0.70. Data were analyzed using frequency counts, percentages, mean, and standard deviation, with 2.50 as the criterion mean. Result: The findings revealed that Yoruba traditional outdoor games promote cultural heritage, indigenous language, and societal values among children. The study also showed that integrating these games supports children’s physical, social, emotional, cognitive, and language development. However, challenges such as limited teacher awareness, digital game influence, inadequate space, poor institutional support, and curriculum exclusion hinder their integration. Conclusion: The study concluded that Yoruba traditional outdoor games are valuable tools for culturally relevant and holistic early childhood education. Their integration into the curriculum should therefore be encouraged and supported by teachers, parents, and policymakers.